Subjective Norms and Behavioral Control; Its Effectiveness On Interest in Sharia Insurance - Najmudin Najmudin; Syihabudin Syihabudin (Jurnal Ilmiah Ekonomi Islam, 2022)
This study aims to analyze (1) the effect of subjective norms on interest in sharia insurance at AXA Mandiri Sharia Bank, (2) the effect of behavioral control on interest in sharia insurance at AXA Mandiri Sharia Bank, and (3) the influence of subjective norms and behavioral control on interest in sharia insurance. at AXA Mandiri Sharia Bank. The object of this research is AXA Mandiri Syariah Insurance. Respondents who became the population of this study were AXA Mandiri Syariah Insurance customers, Serang City, Banten Province. The sample taken in this study amounted to 80 respondents. The research method used is quantitative. Methods of data collection using a questionnaire. Data were analyzed using the multiple linear regression method. The results of this study indicate that (1) subjective norms have a significant positive effect on interest in sharia insurance at AXA Mandiri Sharia Bank, (2) Behavioral control has a significant positive effect on interest in sharia insurance at AXA Mandiri Sharia Bank, and (3) subjective norms and behavioral control have a significant positive effect on interest in sharia insurance at AXA Mandiri Sharia Bank.